2012
DOI: 10.1016/j.visres.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Determining the role of correlated firing in large populations of neurons using white noise and natural scene stimuli

Abstract: The role of correlated firing in representing information has been a subject of much discussion. Several studies in retina, visual cortex, somatosensory cortex, and motor cortex, have suggested that it plays only a minor role, carrying < 10% of the total information carried by the neurons (Gawne and Richmond, 1993; Nirenberg et al., 2001; Oram et al., 2001; Petersen et al., 2001; Rolls et al., 2003). A limiting factor of these studies, however, is that they were carried out using pairs of neurons; how the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 32 publications
8
46
0
Order By: Relevance
“…In this study, we observed the changes in information representation throughout the process of adaptation. Our results show that, at the early stage of the adaptation, the firing rates of neurons conveyed the majority (more than 90%) of the stimulus information, which is in agreement with findings reported by other authors (Meytlis et al 2012;Nirenberg et al 2001;Oizumi et al 2010), whereas at the later stage of the adaptation, the contribution of neural correlation increased remarkably and became the dominant factor, which is in accordance with other research (Schneidman et al 2006). Thus our results reconcile the two different views in the literature and reveal that the contribution of neural correlation in conveying the stimulus information can vary with time during adaptation.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, we observed the changes in information representation throughout the process of adaptation. Our results show that, at the early stage of the adaptation, the firing rates of neurons conveyed the majority (more than 90%) of the stimulus information, which is in agreement with findings reported by other authors (Meytlis et al 2012;Nirenberg et al 2001;Oizumi et al 2010), whereas at the later stage of the adaptation, the contribution of neural correlation increased remarkably and became the dominant factor, which is in accordance with other research (Schneidman et al 2006). Thus our results reconcile the two different views in the literature and reveal that the contribution of neural correlation in conveying the stimulus information can vary with time during adaptation.…”
Section: Discussionsupporting
confidence: 94%
“…However, there is a long-standing debate over the role and significance of concerted activity in neural information processing (Averbeck and Lee 2004). A number of studies have revealed that concerted neuronal activity encodes extra stimulus information which cannot be extracted by the responses of single neurons, and they play important roles in animal behaviors (Dan et al 1998;Ince et al 2010;Ishikane et al 2005), whereas other work suggested that neuronal correlation conveys little information and can be largely neglected (Meytlis et al 2012;Nirenberg et al 2001;Oizumi et al 2010). In this study, we observed the changes in information representation throughout the process of adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, retinotopic maps show experience-dependent plasticity throughout life, allowing them to accommodate changes in the sensory periphery as well as the brain. Current models of activity-dependent mechanisms of topographic map plasticity are based on coactivity rules (4-7), however information in natural scenes may be encoded in additional temporal properties of neuronal firing other than coactivity (8)(9)(10)(11). For instance, temporal features of RGC spiking have been shown to encode information about the visual stimuli (12).…”
mentioning
confidence: 99%
“…In the visual system, populations of retinal ganglion cells (RGCs)-the brain's sole source of visual information-exhibit activity correlations. Previous work has shown that failing to account for these correlations decreases decoded information by 0-20% (Nirenberg et al, 2001;Pillow et al, 2008;Meytlis et al, 2012).…”
Section: Introductionmentioning
confidence: 98%